A high-efficiency permeable water-resistant sand-fixing agent and preparation method thereof

By using a highly efficient penetration-resistant sand fixing agent, combined with a modified styrene acrylic emulsion and a multifunctional additive, the problem of poor penetration effect of existing sand fixing agents is solved, and deeper sand fixing effect and higher water resistance are achieved.

CN119100741BActive Publication Date: 2025-04-11SILICON SOLID NEW MATERIALS (RIZHAO) CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411316789.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-04-11
Estimated Expiration
2044-09-20

AI Technical Summary

Technical Problem

The existing sand fixing agent has poor penetration effect in concrete surface treatment, making it difficult to solidify sand in depth, resulting in the surface fixed but the interior is still loose, which cannot effectively solve the problems of sand and dust.

Method used

High-efficiency penetration-resistant water-resistant sand fixing agents are used, including organic and inorganic silicates, modified styrene acrylic emulsions, dispersion additives, penetration agents, defoaming agents and bactericides. Through the combination of modified styrene acrylic emulsions and multifunctional additives, the permeability and adhesion of the sand fixing agents are improved.

Benefits of technology

It significantly improves the permeability and adhesion of sand fixing agents, and can cure the concrete surface more deeply, solve the problems of sand and ash, and at the same time improve the water resistance of concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005052437950000081
    Figure BDA0005052437950000081
  • Figure BDA0005052437950000091
    Figure BDA0005052437950000091
  • Figure BDA0005052437950000092
    Figure BDA0005052437950000092
Patent Text Reader

Abstract

The invention discloses a high-efficiency permeable water-resistant sand-fixing agent and a preparation method thereof, and relates to the technical field of concrete building materials. The high-efficiency permeable water-resistant sand-fixing agent comprises the following raw materials: organic and inorganic silicate, modified styrene-acrylic emulsion, dispersing aid, penetrant, defoamer, bactericide, water; wherein the modified styrene-acrylic emulsion is prepared from styrene, ethyl methacrylate, methyl acrylate, maleic acid, acrylic acid, and trifluoroethyl methacrylate; the dispersing aid is 2-amino-2-methyl-1-propanol and γ-aminopropyltriethoxysilane, and the mass ratio of the two is 1:1. The present invention further improves the permeability, water resistance and adhesion of the sand-fixing agent by compounding styrene-acrylic emulsion and dispersing aid, improves the sand and dusting effects on the concrete surface, and in the actual application process, can also simplify the wall pretreatment, saving manpower, material and financial resources.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete admixture materials, and particularly relates to a high-efficiency permeable water-resistant sand-fixing agent and a preparation method thereof. Background Art

[0002] In the modern construction process, concrete is the most widely used building material. It not only has the performance characteristics of high strength and good durability, but also has the advantages of wide material sources and low prices. However, in the current use of concrete, due to problems such as concrete proportion, construction and maintenance, it is easy to cause sand and dust on the surface of concrete, making it unable to meet normal functional requirements. Therefore, special surface treatment measures are needed to treat the concrete surface.

[0003] At present, the problems of sand and dust on the concrete surface are mainly treated by sand-fixing materials. In long-term application, it is found that the current sand-fixing primer has poor penetration effect and it is difficult to achieve the ideal effect of deep sand fixation. The surface is fixed, but the inside is still loose sand, which cannot solve the problem of sand and dust. When serious sand and dust occur, the sand and dust parts can only be peeled off, and then sprayed with sand-fixing primer for sealing, which consumes a lot of manpower, material and financial resources. In addition, some concrete is exposed to the outside. After being soaked by rainwater, it will indirectly cause the sand-fixing agent with poor water resistance to lose its sand-fixing effect, and then fall off again, making it difficult to meet the construction requirements.

[0004] The current sand-fixing agent products generally use multiple ingredients such as organic emulsions to achieve the sand-fixing effect. For example, Chinese patent CN105645903A discloses a dust-proof and sand-fixing agent, which is made of the following raw materials in parts by weight: 25-40 parts of colloidal silicon dioxide, 15-20 parts of water, 10-15 parts of titanium dioxide, 11-15 parts of sodium silicate, 8-11 parts of sodium hydroxymethyl cellulose, 2-5 parts of dispersant, 2-5 parts of defoamer, 1-4 parts of thickener, 4-7 parts of preservative, 2-6 parts of cross-linked emulsion, and 2-6 parts of emulsifier. However, when adding the cross-linked emulsion, a large amount of silicon dioxide, titanium dioxide and other ingredients are used, and the emulsion is difficult to disperse and penetrate effectively. After actual preparation, the effect is not ideal.

[0005] Therefore, it is necessary to develop a chemical sand fixation agent with good permeability, good water resistance and high adhesion strength. Summary of the invention

[0006] The main purpose of the invention is to provide a high-efficiency penetrating water-resistant sand-fixing agent and a preparation method. The sand-fixing agent can better penetrate into the interior of concrete, solve the serious sand and dust problems on the surface of road and wall concrete, and improve the water resistance of the concrete surface.

[0007] In order to achieve the above technical objectives, the technical solution adopted by the present invention is:

[0008] A highly efficient permeable water-resistant sand-fixing agent comprises the following raw materials in percentage by mass: 8-22% of organic and inorganic silicate, 15-25% of modified styrene-acrylic emulsion, 0.1-1% of dispersing aid, 0.3-0.6% of penetrant, 0.1-0.5% of defoamer, 0.1%-0.5% of fungicide, and the balance is water, with a total amount of 100%.

[0009] Preferably, the high-efficiency penetrating water-resistant sand-fixing agent comprises the following raw materials in weight ratio: 12-20% organic / inorganic silicate, 15-22% modified styrene-acrylic emulsion, 0.1-0.5% dispersing aid, 0.3-0.5% penetrant, 0.1-0.3% defoamer, 0.1%-0.3% bactericide, and the balance is water, with a total amount of 100%.

[0010] Preferably, the organic-inorganic silicate is a mixture of an organic silicate and an inorganic silicate in a mass ratio of 1:(5-7), wherein the organic silicate is an alkyl sodium silicate or an alkyl potassium silicate, and the inorganic silicate is one or more of sodium silicate, potassium silicate or lithium silicate;

[0011] Preferably, the defoaming agent is one or more of alcohol polyether, emulsified silicone oil, and polyether modified silicone oil; the bactericide is a Kathon bactericide or a VAE bactericide, and the VAE bactericide is a Norfo VAE latex preservative and antibacterial agent, which is commercially available.

[0012] Preferably, the dispersing aid is 2-amino-2-methyl-1-propanol (AMP-95) and γ-aminopropyltriethoxysilane (KH-550), and the mass ratio of the two is 1:1.

[0013] Preferably, the penetrant is composed of fatty alcohol polyoxyethylene ether, propylene glycol, and silane impregnation liquid in a ratio of 5:3:2.

[0014] Preferably, the preparation method of the modified styrene-acrylic emulsion comprises the following steps:

[0015] S1: add water, sodium alkyl sulfonate and fatty amide polyoxyethylene ether into tank A in sequence, stir and dissolve them thoroughly to obtain a mixed emulsion;

[0016] S2 takes 3 / 4 of the mixed emulsion and puts it into tank B. Under constant stirring, slowly add styrene, ethyl methacrylate, methyl acrylate, maleic acid, acrylic acid, and trifluoroethyl methacrylate in the mixed monomers in sequence, and then stirs for 40-50 minutes to obtain a stable pre-emulsion;

[0017] S3: Reactor C starts stirring, and the remaining 1 / 4 of the mixed emulsion, pre-emulsion and deionized water are added, and then nitrogen is introduced, and the displacement is first performed for 20-30 minutes. After the displacement is completed, the temperature is raised to 70-85°C, and potassium persulfate initiator is added, and the reaction is carried out for 35-45 minutes;

[0018] S4 maintains the temperature at 80-85°C, slowly drips the remaining pre-emulsion into tank C, and after the dripping is completed, keeps the temperature for reaction for 2-3 hours, then cools to 30-40°C, adds sodium hydroxide solution to adjust the pH to 7, and filters to obtain the modified styrene-acrylic emulsion.

[0019] More preferably, in step S1, the ratio of water, sodium alkyl sulfonate and fatty amide polyoxyethylene ether is (15-20):1:(1-2).

[0020] More preferably, the mass ratio of the mixed emulsion to the mixed monomer in step S2 is 1:(100-130); the mass ratio of styrene, ethyl methacrylate, methyl acrylate, maleic acid, acrylic acid, and trifluoroethyl methacrylate in the mixed monomer is (20-30):(4-6):(55-70):(3-5):(5-7):(4-8).

[0021] More preferably, in step S3, the ratio of the mixed emulsion, pre-emulsion and deionized water is (3-5):1:(10-15), and the nitrogen flux is 2-3m 3 / h, potassium persulfate initiator accounts for 0.6%-2% of the total amount.

[0022] A method for preparing a highly efficient permeable water-resistant sand-fixing agent comprises the following steps:

[0023] 1) Weigh each component in proportion, mix water and organic / inorganic silicate, and stir evenly to obtain a mixed solution A for standby use.

[0024] 2) Then, add the modified styrene acrylic emulsion, dispersing aid and penetrant into the stirrer and stir for 15-20 minutes to obtain a mixed solution B;

[0025] 3) Add the mixed solution A to the mixed solution B at a rate of 40 L / h. After the addition is completed, continue stirring for 20-30 minutes. Then add the fungicide and defoamer in sequence, stir for 30 minutes respectively, and finally filter the obtained homogeneous solution to prepare a high-efficiency permeable water-resistant sand-fixing agent.

[0026] The present invention has the following beneficial effects:

[0027] (1) First, the present invention introduces multiple functional monomers to prepare a modified styrene-acrylic emulsion, introduces fluorine-containing groups, increases the water resistance and weather resistance of the emulsion after film formation, and solves the problem that the styrene-acrylic emulsion turns white and delaminates in water, thereby losing its adhesive strength;

[0028] (2) Secondly, the present invention introduces two types of additives, namely, multifunctional amine additive AMP-95 and silane coupling agent KH-550. The multifunctional amine additive AMP-95 can adjust the pH value of the emulsion adhesive to make it more stable, and has the effect of wetting and dispersing, thereby promoting the uniform dispersion of effective ingredients such as modified styrene-acrylic emulsion; and the silane coupling agent KH-550, through its coupling function, can effectively enhance the binding force between the modified styrene-acrylic emulsion and the substrate. After the two are mixed in equal proportions, an obvious synergistic effect is produced, thereby achieving a good overall dispersion and adhesion effect of the sand fixation agent;

[0029] (3) In summary, the present invention modifies the traditional styrene acrylic emulsion on the one hand to enhance its adhesion and water resistance and weather resistance, and on the other hand, it is supplemented with AMP-95 and KH-550 to form functional additives to enhance the dispersibility and adhesion of the components such as the diseased styrene acrylic emulsion, thereby achieving a good penetration and sand fixation effect. The raw materials work together to effectively improve the penetration performance of the sand fixation agent, the sand fixation agent has better dispersibility, and the system is more uniform, thereby improving the overall effect of the sand fixation agent. In the actual application process, it can also simplify the wall pretreatment, save manpower, material and financial resources, and meet the different and complex environmental use requirements. The preparation process involved in the present invention is simple and controllable, and can be mass-produced. DETAILED DESCRIPTION

[0030] The technical solution of the present invention is further described below in conjunction with specific embodiments, but is not limited thereto.

[0031] Example 1

[0032] A highly efficient permeable water-resistant sand-fixing agent comprises the following raw materials in weight ratio: 8% organic and inorganic silicate, 15% modified styrene-acrylic emulsion, 0.1% dispersing aid, 0.3% penetrant, 0.1% defoamer, 0.1% bactericide, and the balance is water, with a total amount of 100%.

[0033] The preparation method of modified styrene acrylic emulsion is:

[0034] S1: In tank A, water, sodium alkyl sulfonate and fatty amide polyoxyethylene ether in a mass ratio of 15:1:1 are added in sequence under stirring, and the mixture is fully stirred and dissolved to obtain a mixed emulsion;

[0035] S2: Take 3 / 4 of the mixed emulsion and put it into tank B. Under constant stirring, slowly add styrene, ethyl methacrylate, methyl acrylate, maleic acid, acrylic acid, and trifluoroethyl methacrylate in the mixed monomers in sequence, wherein the mass ratio of the mixed emulsion to the mixed monomers is 1:100, and the mass ratio of styrene, ethyl methacrylate, methyl acrylate, maleic acid, acrylic acid, and trifluoroethyl methacrylate in the mixed monomers is 20:4:55:3:5:4, and then stir for 40 minutes to obtain a stable pre-emulsion;

[0036] S3: Reactor C starts stirring, and the remaining 1 / 4 of the mixed emulsion, part of the pre-emulsion and deionized water are added, and then nitrogen is introduced and replaced for 20 minutes. After the replacement is completed, the temperature is raised to 70°C, and potassium persulfate initiator is added, and the reaction is carried out for 40 minutes; the nitrogen flow rate is 2m 3 / h, the mass ratio of the mixed emulsion, pre-emulsion and deionized water is 3:1:10, and the potassium persulfate initiator accounts for 0.6% of the total amount;

[0037] S4: Maintaining the temperature at 80°C, slowly drop the remaining pre-emulsion into tank C. After the addition is complete, keep the mixture warm for 2 hours, then cool to 30°C, add sodium hydroxide solution to adjust the pH to 7, and filter to obtain the modified styrene-acrylic emulsion.

[0038] The preparation method of the high-efficiency permeable water-resistant sand-fixing agent of this embodiment is as follows:

[0039] S1. Weigh water and organic and inorganic silicates in proportion, stir evenly to obtain a mixed solution A for later use. The organic silicate and the inorganic silicate are alkyl sodium silicate and sodium silicate, respectively, with a mass ratio of 1:5.

[0040] S2. Add modified styrene acrylic emulsion, dispersing aid and penetrant into a stirrer and stir for 15 minutes to obtain mixed solution B. The dispersing aids are AMP-95 and KH-550 in a mass ratio of 1:1; the penetrant is fatty alcohol polyoxyethylene ether, propylene glycol and silane impregnation liquid in a mass ratio of 5:3:2;

[0041] S3. Add the mixed solution A into the mixed solution B at a rate of 40 L / h. Continue stirring for 20 min after the addition is completed. Then add the bactericide Kathon bactericide and the defoaming agent alcohol polyether in sequence, stir for 30 min respectively, and finally filter the obtained homogeneous solution to prepare a high-efficiency penetrating water-resistant sand-fixing agent.

[0042] Example 2

[0043] A highly efficient penetrating water-resistant sand-fixing agent comprises the following raw materials in weight ratio: 12% organic and inorganic silicate, 15% modified styrene-acrylic emulsion, 0.2% dispersing aid, 0.3% penetrant, 0.1% defoamer, 0.1% bactericide, and the balance is water, and the total amount is 100%.

[0044] The preparation method of modified styrene acrylic emulsion is:

[0045] S1: In tank A, water, sodium alkyl sulfonate and fatty amide polyoxyethylene ether in a ratio of 16:1:2 are added in sequence under stirring, and the mixture is fully stirred and dissolved to obtain a mixed emulsion;

[0046] S2: Take 3 / 4 of the mixed emulsion and put it into tank B. Under constant stirring, slowly add styrene, ethyl methacrylate, methyl acrylate, maleic acid, acrylic acid, and trifluoroethyl methacrylate in the mixed monomers in sequence, wherein the mass ratio of the mixed emulsion to the mixed monomers is 1:110, and the ratio of styrene, ethyl methacrylate, methyl acrylate, maleic acid, acrylic acid, and trifluoroethyl methacrylate in the mixed monomers is 20:5:65:4:6:7, and then stir for 45 minutes to obtain a stable pre-emulsion;

[0047] S3: Reactor C starts stirring, and the remaining 1 / 4 of the mixed emulsion, part of the pre-emulsion and deionized water are added, and then nitrogen is introduced and replaced for 20 minutes. After the replacement is completed, the temperature is raised to 78°C, and potassium persulfate initiator is added, and the reaction is carried out for 40 minutes; the nitrogen flow rate is 2.5m 3 / h, the ratio of mixed emulsion, pre-emulsion and deionized water is 3:1:12, and potassium persulfate initiator accounts for 0.9% of the total;

[0048] S4: Maintaining the temperature at 85°C, slowly drop the remaining pre-emulsion into tank C. After the addition is complete, keep the reaction warm for 2.5 hours, then cool to 35°C, add sodium hydroxide solution to adjust the pH to 7, and filter to obtain the modified styrene-acrylic emulsion.

[0049] The preparation method of the high-efficiency permeable water-resistant sand-fixing agent of this embodiment is as follows:

[0050] S1. Weigh water and organic and inorganic silicates in proportion, stir evenly to obtain a mixed solution A for later use. The organic silicate and the inorganic silicate are potassium alkyl silicate and potassium silicate, respectively, with a mass ratio of 1:5.

[0051] S2. Add modified styrene acrylic emulsion, dispersing aid and penetrant into a stirrer and stir for 20 minutes to obtain mixed solution B. The dispersing aids are AMP-95 and KH-550 in a mass ratio of 1:1; the penetrant is fatty alcohol polyoxyethylene ether, propylene glycol and silane impregnation liquid in a ratio of 5:3:2;

[0052] S3. Add the mixed solution A into the mixed solution B at a rate of 40 L / h. Continue stirring for 30 min after the addition is completed. Then add the fungicide VAE fungicide and the defoaming agent emulsified silicone oil in sequence, stir for 30 min respectively, and finally filter the obtained homogeneous solution to prepare a high-efficiency penetrating water-resistant sand-fixing agent.

[0053] Example 3

[0054] A highly efficient penetrating water-resistant sand-fixing agent comprises the following raw materials in weight ratio: 16% of organic and inorganic silicate, 19% of modified styrene-acrylic emulsion, 0.4% of dispersing aid, 0.3% of penetrant, 0.1% of defoamer, 0.1% of fungicide, and the balance is water, with a total amount of 100%.

[0055] The preparation method of modified styrene acrylic emulsion is:

[0056] S1: In tank A, water, sodium alkyl sulfonate and fatty amide polyoxyethylene ether in a mass ratio of 16:1:2 are added in sequence under stirring, and the mixture is fully stirred and dissolved to obtain a mixed emulsion;

[0057] S2: Take 3 / 4 of the mixed emulsion and put it into tank B. Under constant stirring, slowly add styrene, ethyl methacrylate, methyl acrylate, maleic acid, acrylic acid, and trifluoroethyl methacrylate in the mixed monomers in sequence, wherein the mass ratio of the mixed emulsion to the mixed monomers is 1:100, and the mass ratio of styrene, ethyl methacrylate, methyl acrylate, maleic acid, acrylic acid, and trifluoroethyl methacrylate in the mixed monomers is 20:5:65:3:5:7, and then stir for 45 minutes to obtain a stable pre-emulsion;

[0058] S3: Reactor C starts stirring, and the remaining 1 / 4 of the mixed emulsion, part of the pre-emulsion and deionized water are added, and then nitrogen is introduced and replaced for 20 minutes. After the replacement is completed, the temperature is raised to 78°C, and potassium persulfate initiator is added, and the reaction is carried out for 40 minutes; the nitrogen flow rate is 2.5m 3 / h, the mass ratio of the mixed emulsion, pre-emulsion and deionized water is 3:1:12, and the potassium persulfate initiator accounts for 0.9% of the total amount;

[0059] S4: Maintaining the temperature at 85°C, slowly drop the remaining pre-emulsion into tank C. After the addition is complete, keep the reaction warm for 2.5 hours, then cool to 35°C, add sodium hydroxide solution to adjust the pH to 7, and filter to obtain the modified styrene-acrylic emulsion.

[0060] The preparation method of the high-efficiency permeable water-resistant sand-fixing agent of this embodiment is as follows:

[0061] S1. Weigh water and organic and inorganic silicates in proportion, stir evenly to obtain a mixed solution A for later use. The organic silicate and the inorganic silicate are potassium alkyl silicate and potassium silicate, respectively, with a mass ratio of 1:5.

[0062] S2. Add modified styrene acrylic emulsion, dispersing aid and penetrant into a stirrer and stir for 20 minutes to obtain mixed solution B. The dispersing aids are AMP-95 and KH-550 in a mass ratio of 1:1; the penetrant is fatty alcohol polyoxyethylene ether, propylene glycol and silane impregnation liquid in a mass ratio of 5:3:2;

[0063] S3. Add the mixed solution A into the mixed solution B at a rate of 40 L / h. Continue stirring for 30 min after the addition is completed. Then add the Kathon fungicide and defoaming agent emulsified silicone oil in sequence, stir for 30 min respectively, and finally filter the obtained homogeneous solution to prepare a high-efficiency penetrating water-resistant sand-fixing agent.

[0064] Example 4

[0065] A highly efficient penetrating water-resistant sand-fixing agent comprises the following raw materials in weight ratio: 20% organic and inorganic silicate, 22% modified styrene-acrylic emulsion, 0.5% dispersing aid, 0.5% penetrant, 0.3% defoamer, 0.3% bactericide, and the balance is water, with a total amount of 100%.

[0066] The preparation method of modified styrene acrylic emulsion is:

[0067] S1: In tank A, water, sodium alkyl sulfonate and fatty amide polyoxyethylene ether in a mass ratio of 20:1:2 are added in sequence under stirring, and the mixture is fully stirred and dissolved to obtain a mixed emulsion;

[0068] S2: Take 3 / 4 of the mixed emulsion and put it into tank B. Under constant stirring, slowly add styrene, ethyl methacrylate, methyl acrylate, maleic acid, acrylic acid, and trifluoroethyl methacrylate in the mixed monomers in sequence. The mass ratio of the mixed emulsion to the mixed monomers is 1:130, and the ratio of styrene, ethyl methacrylate, methyl acrylate, maleic acid, acrylic acid, and trifluoroethyl methacrylate in the mixed monomers is 25:5:65:3:5:7. Then stir for 45 minutes to obtain a stable pre-emulsion.

[0069] S3: Reactor C starts stirring, and the remaining 1 / 4 of the mixed emulsion, part of the pre-emulsion and deionized water are added, and then nitrogen is introduced and replaced for 20 minutes. After the replacement is completed, the temperature is raised to 85°C, and potassium persulfate initiator is added, and the reaction is carried out for 45 minutes; the nitrogen flow rate is 2.5m 3 / h, the mass ratio of the mixed emulsion, pre-emulsion and deionized water is 5:1:15, and the potassium persulfate initiator accounts for 2% of the total;

[0070] S4: Maintaining the temperature at 85°C, slowly drop the remaining pre-emulsion into tank C. After the addition is complete, keep the reaction warm for 2.5 hours, then cool to 33°C, add sodium hydroxide solution to adjust the pH to 7, and filter to obtain the modified styrene-acrylic emulsion.

[0071] The preparation method of the high-efficiency permeable water-resistant sand-fixing agent of this embodiment is as follows:

[0072] S1. Weigh water and organic and inorganic silicates in proportion, stir evenly to obtain a mixed solution A for later use. The organic silicate and the inorganic silicate are respectively alkyl sodium silicate and potassium silicate, with a mass ratio of 1:7;

[0073] S2. Add modified styrene acrylic emulsion, dispersing aid and penetrant into a stirrer and stir for 20 minutes to obtain mixed solution B. The dispersing aids are AMP-95 and KH-550 in a mass ratio of 1:1; the penetrants are fatty alcohol polyoxyethylene ether, propylene glycol and silane impregnation liquid in a mass ratio of 5:3:2;

[0074] S3. Add the mixed solution A into the mixed solution B at a rate of 40 L / h. Continue stirring for 25 min after the addition is completed. Then add the bactericide Kathon bactericide and the defoaming agent polyether modified silicone oil in sequence, stir for 30 min respectively, and finally filter the obtained homogeneous solution to prepare a high-efficiency penetrating water-resistant sand-fixing agent.

[0075] Example 5

[0076] A highly efficient penetrating water-resistant sand-fixing agent comprises the following raw materials in weight ratio: 22% organic and inorganic silicate, 25% modified styrene-acrylic emulsion, 1% dispersing aid, 0.6% penetrant, 0.5% defoamer, 0.5% bactericide, and the balance is water, with a total amount of 100%.

[0077] The preparation method of modified styrene acrylic emulsion is:

[0078] S1: In tank A, water, sodium alkyl sulfonate and fatty amide polyoxyethylene ether in a mass ratio of 20:1:2 are added in sequence under stirring, and the mixture is fully stirred and dissolved to obtain a mixed emulsion;

[0079] S2: Take 3 / 4 of the mixed emulsion and put it into tank B. Under constant stirring, slowly add styrene, ethyl methacrylate, methyl acrylate, maleic acid, acrylic acid, and trifluoroethyl methacrylate in the mixed monomers in sequence, wherein the mass ratio of the mixed emulsion to the mixed monomers is 1:130, and the mass ratio of styrene, ethyl methacrylate, methyl acrylate, maleic acid, acrylic acid, and trifluoroethyl methacrylate in the mixed monomers is 30:6:70:5:7:8, and then stir for 50 minutes to obtain a stable pre-emulsion;

[0080] S3: Reactor C starts stirring, and the remaining 1 / 4 of the mixed emulsion, part of the pre-emulsion and deionized water are added, and then nitrogen is introduced and replaced for 30 minutes. After the replacement is completed, the temperature is raised to 85°C, and potassium persulfate initiator is added, and the reaction is carried out for 45 minutes; the nitrogen flow rate is 3m 3 / h, the ratio of mixed emulsion, pre-emulsion and deionized water is 5:1:15, and potassium persulfate initiator accounts for 2% of the total;

[0081] S4: Maintaining the temperature at 85°C, slowly drop the remaining pre-emulsion into tank C. After the addition is complete, keep the reaction warm for 2.5 hours, then cool to 33°C, add sodium hydroxide solution to adjust the pH to 7, and filter to obtain the modified styrene-acrylic emulsion.

[0082] The preparation method of the high-efficiency permeable water-resistant sand-fixing agent of this embodiment is as follows:

[0083] S1. Weigh water and organic and inorganic silicates in proportion, stir evenly to obtain a mixed solution A for later use. The organic silicate and the inorganic silicate are respectively alkyl potassium silicate and lithium silicate, with a ratio of 1:7;

[0084] S2. Add modified styrene acrylic emulsion, dispersing aid and penetrant into a stirrer and stir for 20 minutes to obtain mixed solution B. The dispersing aid is AMP-95 and KH-550 in a ratio of 1:1; the penetrant is fatty alcohol polyoxyethylene ether, propylene glycol and silane impregnation liquid in a ratio of 5:3:2;

[0085] S3. Add the mixed solution A into the mixed solution B at a rate of 40 L / h. Continue stirring for 25 min after the addition is completed. Then add the fungicide VAE fungicide and the defoaming agent alcohol polyether in sequence, stir for 30 min respectively, and finally filter the obtained homogeneous solution to prepare a high-efficiency penetrating water-resistant sand-fixing agent.

[0086] Comparative Example 1

[0087] In the formulation and preparation method of this comparative example, except that only AMP-95 is used as the dispersing aid, the rest are the same as those of Example 3.

[0088] Comparative Example 2

[0089] In the formulation and preparation method of this comparative example, except that only KH-550 is used as the dispersing aid, the rest are the same as those of Example 3.

[0090] Comparative Example 3

[0091] In the comparative example formulation and preparation method, the dispersing aids are AMP-95 and KH-550, and the mass ratio of the two is 2:1. The rest is the same as in Example 3.

[0092] Comparative Example 4

[0093] In the comparative example formulation and preparation method, the dispersing aids are AMP-95 and KH-550, and the mass ratio of the two is 1:2. The rest is the same as in Example 3.

[0094] Comparative Example 5

[0095] In the formula and preparation method of this comparative example, except for using common commercially available styrene-acrylic emulsion, the rest is the same as Example 3. This comparative example uses commercially available conventional styrene-acrylic emulsion with a solid content of 50±1%, a viscosity of 2000S, and a model of BASF-Anguli PS608.

[0096] Performance Testing

[0097] The penetration depth test of the sand-fixing agent was carried out on Examples 1-5 and Comparative Examples 1-5. The specific experimental steps are as follows: the prepared sand-fixing agent was brushed onto the surface of the concrete test block, cured for 24 hours, and then soaked in water at room temperature for 72 hours. After being taken out, it was cut crosswise along the brushed surface. The height not penetrated by water was the penetration depth of the sand-fixing agent. The data of each group of experiments were recorded in Table 1.

[0098] Table 1 Data record table of each group of experiments

[0099]

[0100]

[0101] It can be seen from Table 1 that the addition of the compounded sand-fixing agent of different embodiments of the present invention can improve the penetration ability of the sand-fixing agent, and the penetration depth of the embodiments is significantly higher than that of Comparative Example 1 and Comparative Example 2 in which the dispersing agent is added alone, indicating that the compounded sand-fixing agent can better assist the sand-fixing agent to penetrate into the interior due to the addition of two different types of additives, thereby improving the sand-fixing performance of the sand-fixing agent on concrete. And it can be seen from Example 3 and Comparative Example 3 and Comparative Example 4 in Table 1 that the compounded sand-fixing agent has better penetration ability when the mass ratio of the two dispersing additives is 1:1.

[0102] The water resistance and wear resistance of Examples 1-5 and Comparative Examples 1-5 were subjected to wear resistance tests. The specific experimental steps are as follows: select concrete test blocks, six blocks in each group, weigh a certain amount of sand and spread it on the surface of the concrete test blocks, spray the sand-fixing agent of Examples 1-5 and Comparative Examples 1-5 onto the concrete surface, and select three concrete test blocks from each group after curing for 24 hours and soak them in water for 72 hours. The remaining three blocks in each group are not immersed in water. Wear resistance tests were conducted on all concrete test blocks, and the data of each group of experiments were recorded in Table 2. The wear resistance test of concrete was carried out in accordance with GB / T16925-1997, "Test Method for Wear Resistance of Concrete and Its Products (Ball Bearing Method)". This method uses a ball bearing wear tester with a ball bearing as the grinding head. When the ball rotates and rolls under the rated load, it rubs the surface of the wet test piece and grinds an annular grinding groove on the worn surface. The wear resistance is calculated by measuring the depth of the grinding groove and the grinding number of the grinding head, as shown in the formula:

[0103]

[0104] Wherein, Ia is the wear resistance, accurate to 0.01; R is the number of revolutions of the grinding head, in thousand revolutions; P is the grinding groove depth (final grinding groove depth - initial grinding groove depth), in mm.

[0105] Table 2 Abrasion resistance of concrete surface before and after using sand fixation agent

[0106]

[0107] It can be seen from Table 2 that the wear resistance of the embodiment after immersion in water is slightly reduced, while the wear resistance of comparative example 5 after immersion in water is significantly reduced, indicating that the polymer obtained by polymerization of trifluoroethyl methacrylate in the modified styrene acrylic emulsion with trifluoroethyl methacrylate has fluorine atoms on the side chain and has excellent water resistance. In addition, compared with Example 3 and Comparative Examples 1-4, the wear resistance of Example 3 after immersion in water is significantly better than that of Comparative Examples 1-4, indicating that the ratio of the two dispersing aids in Example 3 makes the dispersibility system of the sand-fixing agent more uniform and has better water resistance and anti-seepage effect. The above results show that the product of the present invention with the addition of the modified styrene acrylic emulsion and the two dispersing aids in a weight ratio of 1:1 can better improve the water resistance of the sand-fixing agent after curing, and can still maintain good sand-fixing performance after immersion in water.

[0108] The adhesion of the sand-fixing agents of Examples 1-5 and Comparative Examples 1-5 to concrete was tested according to "GB / T5210-2006 Paint and Varnish Pull-Off Adhesion Test", and the resistance to chloride ion penetration was tested according to "JT-T 695-2007 Technical Conditions for Anticorrosion of Surface Coatings of Concrete Bridge Structures".

[0109] Each group of samples was tested 6 times, and the results were averaged. The data of each group of experiments are recorded in Table 3.

[0110] Table 3 Adhesion of concrete surface after using sand fixation agent

[0111]

[0112] It can be clearly seen from Table 3 that compared with the pull-out strength of the conventional product on the market, namely the product of Comparative Example 5, the use of the products of Examples 1-5 can significantly improve the adhesion of the concrete base surface, achieve a good curing effect, and the concrete samples treated by the examples show good resistance to chloride ion corrosion. In addition, compared with Comparative Examples 1-4, the pull-out strength and chloride ion penetration resistance of Example 3 are both higher than those of Comparative Examples 1-4, indicating that the use of two different types of dispersants promotes the uniform dispersion of modified styrene acrylic emulsion and other functional raw materials, and achieves an overall improvement in adhesion and anti-corrosion performance. In Comparative Examples 1-4, which change the dispersant composition, and Comparative Example 5, which changes the emulsion composition, the synergistic balance between the raw materials is broken, and thus the effect is weakened.

[0113] In summary, in actual use, the sand-fixing agent of the embodiment of the present invention can better solve the problem of sand and dust on the concrete surface, and its sand-fixing performance is excellent. Embodiment 3 is the best embodiment of this test, which is easy to use and suitable for popularization and application.

[0114] It should be noted that the above embodiments are only partial embodiments of the preferred methods of implementing the present invention, rather than all embodiments. Obviously, based on the above embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

Claims

1. A highly efficient permeable water-resistant sand-fixing agent, characterized in that: The invention comprises the following raw materials in percentage by weight: 8-22% of organic and inorganic silicate, 15-25% of modified styrene-acrylic emulsion, 0.1-1% of dispersing aid, 0.3-0.6% of penetrant, 0.1-0.5% of defoamer, 0.1%-0.5% of fungicide, and the balance is water, and the total amount is 100%; the preparation method of the modified styrene-acrylic emulsion comprises the following steps: S1: adding water, sodium alkyl sulfonate and fatty amide polyoxyethylene ether in turn into tank A under stirring conditions, stirring and dissolving them fully to obtain a mixed emulsion; S2: Take 3 / 4 of the mixed emulsion and put it into tank B. Under constant stirring, slowly add styrene, ethyl methacrylate, methyl acrylate, maleic acid, acrylic acid, and trifluoroethyl methacrylate in the mixed monomers in sequence, and then stir for 40-50 minutes to obtain a stable pre-emulsion; S3: Reactor C starts stirring, and the remaining 1 / 4 of the mixed emulsion, part of the pre-emulsion and deionized water are added, and then nitrogen is introduced, and displacement is first performed for 20-30 minutes. After the displacement is completed, the temperature is raised to 70-85°C, and potassium persulfate initiator is added, and the reaction is carried out for 35-45 minutes; S4: maintaining the temperature at 80-85°C, slowly dripping the remaining pre-emulsion into tank C, keeping the temperature for reaction for 2-3h after the dripping is completed, then cooling to 30-40°C, adding sodium hydroxide solution to adjust the pH to 7, filtering to obtain a modified styrene-acrylic emulsion; the mass ratio of water, sodium alkyl sulfonate, and fatty amide polyoxyethylene ether in step S1 is (15-20): 1: (1-2); the mass ratio of the mixed emulsion to the mixed monomer in step S2 is 1: (100-130); the mass ratio of the mixed monomer is 1: (100-130); The mass ratio of styrene, ethyl methacrylate, methyl acrylate, maleic acid, acrylic acid and trifluoroethyl methacrylate is (20-30): (4-6): (55-70): (3-5): (5-7): (4-8); the ratio of the mixed emulsion, pre-emulsion and deionized water in step S3 is (3-5): 1: (10-15); the amount of potassium persulfate initiator used is 0.6%-2% of the total mass of the substances in the reaction tank C; the flow rate of the introduced nitrogen is 2-3m³ / h.

2. The high-efficiency permeable water-resistant sand-fixing agent according to claim 1, characterized in that: The organic-inorganic silicate is obtained by mixing an organic silicate and an inorganic silicate in a mass ratio of 1:(5-7), wherein the organic silicate is alkyl sodium silicate or alkyl potassium silicate, and the inorganic silicate is one or more of sodium silicate, potassium silicate or lithium silicate.

3. The high-efficiency permeable water-resistant sand-fixing agent according to claim 1, characterized in that: The defoaming agent is one or more of alcohol polyether, emulsified silicone oil and polyether modified silicone oil.

4. The high-efficiency permeable water-resistant sand-fixing agent according to claim 1, characterized in that: The bactericide is Kathon bactericide or VAE bactericide; the dispersing aid is 2-amino-2-methyl-1-propanol and γ-aminopropyltriethoxysilane, and the mass ratio of the two is 1:

1.

5. The high-efficiency permeable water-resistant sand-fixing agent according to claim 1, characterized in that: The penetrant is composed of fatty alcohol polyoxyethylene ether, propylene glycol and silane impregnation liquid in a ratio of 5:3:2, wherein the silane impregnation liquid is isobutyl triethoxy silane impregnation agent.

6. A method for preparing the highly efficient permeable water-resistant sand-fixing agent according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. Weigh the components in proportion, mix water and organic and inorganic silicate, and stir to obtain a mixed solution A; S2. Add the modified styrene-acrylic emulsion, dispersing aid and penetrant into a stirrer and stir for 15-20 min to obtain a mixed solution B; S3. Add mixed liquid A to mixed liquid B at a rate of 40L / h. Continue stirring for 20-30min after the addition is completed. Then add fungicide and defoamer in sequence, stir for 30min respectively, and finally filter to obtain a homogeneous solution, i.e., the finished product of high-efficiency penetrating water-resistant sand-fixing agent.

Citation Information

Patent Citations

  • Dust-prevention and sand-fixation agent

    CN105645903A

  • Novel waterproof agent and method for preparing same

    CN107163643A

  • High-permeability sand-fixing primer

    CN113667329A